The fish community of Palo Seco Reef, Veracruz, gulf of Mexico and its relationship with the morpho functional groups - González-Gándara, Carlos (Universidad Autónoma de Tamaulipas, 2020)
The submerged reef banks may play the part of germoplasm reserve, due to their richness and species abundance that contribute to the biomass development in adjacent emergent reefs. The goal of this research was to establish the fish community of Palo Seco Reef, Veracruz, Mexico, and its relationship with morpho functional groups of the substrate. One hundred and seventeen visual censuses (63 random and 54 belt-transects) using SCUBA dive equipment were carried out during the Summers of 2013 and 2016 in order to determine the fish community structure (components, richness, abundance, biomass and trophic guilds) and characterize the substrate based on the morpho functional groups (MFG). The relationships between the fish and the substrate were determined by a canonical correspondence analysis (CCA). The ichthyofaune was represented by109 species, including 2 invasive species (Pterois volitans and Neopomacentrus cyanomos), and 3 endemic species of Veracruz (Elacatinus jarocho, Hypoplectrus atlahua and Hypoplectrus castroaguirrei). Halichoeres burekae, Coryphopterus hyalinus and juvenile of Haemulon aurolineatum were the most abundant species, whereas Sphyraena barracuda, Anisotremus virginicus and Megalops atlanticus dominated in biomass. The zooplanctivore guild was the most abundant (83.35 %), in contrast with the herbivorous (1.24 %). The piscivorous fish were the most abundant in biomass (28.89 %), followed by the generalized carnivorous fish (28.22 %). Nine MFG characterized the substrate of Palo Seco Reef. The CCA showed a gradient of MFG and depth which were related to some fish species and to some trophic guilds. The ichthyological community of Palo Seco Reef is similar to the fish communities of other reefs in Veracruz, but its richness and abundance respond to the local environment. The similarity suggests a possible regional connectivity and underlines its importance for conservation.